Signs of the zodiac : a modern guide to the age-old wisdom of the stars - Santos, Carlota (Artisan, 2022)
"In this beautifully illustrated astrology handbook, author and artist Carlota Santos guides readers on an astral journey through the constellations. Included are expansive zodiac sign profiles that cover the important details-personality summaries, compatibility charts, and the structure and story behind each sign--as well as representative tarot cards, amulets to balance each sign's qualities, and rituals to nurture positive traits. For those looking to dig deeper and explore their full astrological chart, Santos shares her celestial knowledge on everything from the relationships between planets and their rulers to the phases of the moon, from ascendents and descendants to the twelve houses. With this valuable material at their disposal, readers are guided to create their own birth charts as a closing ritual, using beautifully illustrated fill-in pages"--